Penerapan Game Theory dalam Menentukan Strategi Pemberian Vaksin Covid-19 yang Optimal di Indonesia - Ahmad Sultan Chaeruddin; Icih Sukarsih; Onoy Rohaeni (UNISBA Press, 2022)
Abstract. The COVID-19 pandemic has entered Indonesia since early March 2020. Various efforts made by the government to prevent the spread of this virus, are deemed not effective enough. One strategy that is considered capable of fighting the virus is through a vaccination program, because the vaccine will create herd immunity. However, the presence of viral mutations affects the efficacy of existing vaccines. For this reason, the government must choose the optimal strategy for vaccination. This study aims to determine the optimal proportion of the use of Sinovac and AstraZeneca vaccines using Game Theory, and determine the level of herd immunity that will be achieved if the government only uses these two vaccines. In this case, it is assumed that the Government is a line player with this type of vaccine (Sinovac and AstraZeneca) as the strategy, and Virus as a column player with its variants (old and new) as the strategy. While the efficacy of each type of vaccine is seen as a game value. This problem can be modeled into a 2×2 payoff matrix which can be solved using a mixed strategy. Based on the results of the study, it was found that the Government's optimal strategy was to vaccinate 86.1% of its citizens with Sinovac and 13.9% of its citizens with AstraZeneca. Through this optimal strategy, the herd immunity achieved is 66.7% of the total population. Abstrak. Pandemi COVID-19 telah masuk ke Indonesia sejak awal Maret 2020. Berbagai upaya yang dilakukan pemerintah untuk mencegah penyebaran virus ini, dirasa belum cukup efektif. Salah satu strategi yang dianggap mampu untuk melawan virus adalah melalui program vaksinasi, karena vaksin akan menciptakan herd immunity. Namun, adanya mutasi virus mempengaruhi efikasi vaksin yang ada. Untuk itu pemerintah harus memilih strategi yang optimal dalam melakukan vaksinasi. Penelitan ini bertujuan untuk menentukan proporsi optimal penggunaan vaksin Sinovac dan AstraZeneca menggunakan Game Theory, dan mengetahui tingkat herd immunity yang akan dicapai jika pemerintah hanya menggunakan kedua vaksin tersebut.. Dalam hal ini diasumsikan bahwa Pemerintah sebagai pemain baris dengan jenis vaksin (Sinovac dan AstraZeneca) sebagai strateginya, dan Virus sebagai pemain kolom dengan variannya (lama dan baru) sebagai strateginya. Sedangkan efikasi dari masing-masing jenis vaksin dipandang sebagai nilai permainan. Masalah ini dapat dimodelkan kedalam matriks payoff berukuran yang dapat diselesaikan menggunakan strategi campuran. Berdasarkan hasil penelitian diperoleh bahwa strategi optimal Pemerintah adalah melakukan vaksinasi terhadap 86,1% warganya dengan Sinovac dan 13,9% warganya dengan AstraZeneca. Melalui strategi optimal tersebut, herd immunity yang dicapai adalah 66,7% dari total populasi.